Isolation of rosmarinic acid and methyl rosmarinate as lipoxygenase inhibitors from Salvia palaestina Benth. by activity-guided fractionation - Icen, Mehmet Sina; Gurbuz, Ilhan; Bedir, Erdal; Gunbatan, Tugba; Demirci, Fatih (Elsevier, 2021)
Salvia palaestina aqueous and methanol extracts were prepared from the aerial parts, which were evaluated for the in vitro anti-inflammatory properties using the lipoxygenase (LO) enzyme inhibition assay. While the aqueous extract showed no activity at test concentrations, a significant (p < 0.001) lipoxygenase inhibition was detected for the methanol extract with 29% inhibition. Activity guided fractionation was carried out on the methanol extract via liquid-liquid partitioning using n-hexane, dichloromethane, ethyl acetate, and n-butanol. The ethyl acetate fraction showed statistically the best inhibition among the sub-fractions with 70% inhibition (p < 0.0001). The compounds responsible for the activity were purified, and their structures were established as rosmarinic acid, and methyl rosmarinate by spectroscopic methods. IC50 values of rosmarinic acid, and methyl rosmarinate were calculated as 0.21 and 0.02 mu M, respectively. In conclusion, the in vitro anti-inflammatory potential of S. palaestina was associated to rosmarinic acid, and methyl rosmarinate, for the first time to the best of our knowledge. (C) 2021 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Salvia palaestina; Lipoxygenase; Activity-guided fractionation; Rosmarinate; Anti-inflammatory activity